A Descriptive Analysis of the Translation Strategies for the Word Like - Zulfah, Annisa Siti; Setiarini, Ni Luh Putu (ITScience (Information Technology and Science), 2025)
The translation of the word like into Indonesian is the focus of descriptive analytical study. The problem of this research is: What is the translation of the word like in Indonesian and what are the strategies applied in translating the word? The aim of this study is to find out the translation of the word like in Indonesian and the strategies applied in translating the word. The sources of the data in this research were “It Ends with Us” novel by Colleen Hoover and its translation. The data were the words like found in the English version of this novel and the Indonesian translation. This study employed mixed methods, they were quantitative and qualitative with descriptive analytical approach. The result revealed that out of 75 data analyzed, only nine translation strategies were used in the analysis of the data; they were: literal translation (14 data), unit shift (3 data), transposition (16 data), antonymy (1 data), synonymy (11 data), paraphrase (22 data), emphasis (3 data), repetition (4 data), and clause structure change (1 data). The most dominant strategy used in the analysis is paraphrase. Moreover, out of six principles of translation, there were three kinds applied, namely meaning, form, and idiom.